Polimorfismo de VNTR na região promotora do gene DGAT1 em bovinos leiteiros, caprinos e ovinos - Luizetti, Fabiane (2010)
The DGAT1 gene is a candidate gene involved in fat content in milk and due to its physiological function, this gene is of great interest for dairy cattle improvement. This gene presents a VNTR region with little information, but it suggests that the polymorphism in this region may be related to variations in production. This study analyzed DNA samples from 72 dairy cattle using blood samples taken from tail vein of animals. The genotype and gene frequency of VNTR polymorphism in the DGAT1 gene was obtained directly after PCR amplification. It was found four alleles present in homozygous and heterozygous, whose frequencies were: allele 1 (with three repetitions) of 4%, allele 2 (with four repetitions) of 50%, allele 3 (with five repetitions) of 40% and allele 4 (with six repetitions) of 6%. It was verified the Hardy-Weinberg equilibrium by Chi-square test concluding that the population was not in balance. Most studies on DGAT1 are made in cattle due to its higher representation in milk production. However, goats and sheep also have a production of milk in the market. Using the primers designed previously for the bovine species, the amplified fragments of the promoter region of DGAT1 gene were compared in cattle, goats and sheep. The extraction of genomic DNA was made from blood samples. The primers designed were not efficient, because although the region expected amplified with fragments between 700 and 800 base pairs in the three species, a small percentage of the individuals had any result, which probably occurred due to the high nucleotide variation in the region of annealing primers. There were found a VNTR polymorphism in the promoter region of the DGAT1 gene in Alpine and Saanen breeds.